The BabelNEG System - A Protocol-generic Infrastructure for Electronic SLA Negotiations in the Internet of Services - Sebastian Hudert (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2011)
Visions of the next-generation Internet of Services are driven by digital resources traded on a global scope. For the resulting economic setting, automated on-line techniques for handling services and resources themselves, for advertising and discovering as well as for the on-the-fly negotiation of proper terms for their use are needed. Hence, a flexible infrastructure for the respective management of services and associated service level agreements is mandatory. This thesis presents the results of my dissertation project. They comprise a service infrastructure, able to support the structured discovery and protocol-generic negotiation of electronic service level agreements (SLAs) and thus services themselves. (...) – – Sowohl die Wissenschaft als auch die industrielle Praxis sehen elektronische Dienste und Ressourcen, die auf globalen digitalen Marktplätzen gehandelt werden als fundamentale Konzepte des zukünftigen Internets der Dienste an. In einem solchen ökonomischen Umfeld werden Mechanismen zum automatisierten Management der beteiligten Ressourcen, zum Veröffentlichen und Auffinden, wie auch zum direkten Verhandeln dieser digitalen Güter essentiell. In dieser Dissertationsschrift werden die Ergebnisse meiner Arbeit an diesem Forschungsproblem dargestellt. Ich beschreibe die von mir entwickelte Softwareinfrastruktur, die ein strukturiertes Veröffentlichen und Protokoll-generisches Verhandeln elektronischer Dienstverträge (Service Level Agreements, kurz SLAs), und damit auch der Dienste selbst, ermöglicht. (...)
urn:nbn:de:bvb:703-opus-9287
Keywords: 004